Development of a toolkit for telenutrition in follow-up for cardiovascular disease - Valentina Pierattini; Barbara Biffi; Susanna Agostini; Silvia Brazzo; Maria Luisa Masini; Francesco Fattirolli; Letizia da Vico (Università degli Studi di Torino, 2023)
INTRODUCTION To ensure the continuity of nutritional care in Cardiovascular Rehabilitation (CR) during the COVID-19 epidemic emergency, a toolkit for telenutritional follow-up was developed for patients at nutritional risk and patients with modifiable risk factors related to eating habits. The reference method for this work is represented by the Nutrition Care Process and Terminology by the Academy of Nutrition and Dietetics (AND), which pursues the goal of implementing safe, effective, person-centred, timely, efficient and equitable nutritional care. MATERIALS AND METHODS The toolkit is composed of digital records for nutritional teleconsultation aimed at the most fragile (at risk for malnutrition), or overweight/obese, diabetic, dyslipidemic, hypertensive patients. In addition, it provides tools and educational/informative material useful to patients for carrying out the telephone consultation/video call. CONCLUSIONS This work - and telenutrition in general - could optimize the effectiveness of nutritional care and patient's adherence, by reducing distances, waiting times, costs and other inconveniences. Our future goal is to develop a research project involving CR centers to establish the effectiveness of using the toolkit in clinical practice, in terms of desired outcomes and follow-up dedicated time.